2009
DOI: 10.1002/mnfr.200800456
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hydrogen peroxide in cell culture media by apple polyphenols and its effect on antioxidant biomarkers in the colon cell line HT‐29

Abstract: Beneficial health effects of diets containing fruits have partly been attributed to polyphenols which display a spectrum of bioactive effects, including antioxidant activity. However, polyphenols can also exert prooxidative effects in vitro. In this study, polyphenol-mediated hydrogen peroxide (H(2)O(2)) formation was determined after incubation of apple juice extracts (AEs) and polyphenols in cell culture media. Effects of extracellular H(2)O(2 )on total glutathione (tGSH; =GSH + GSSG) and cellular reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 42 publications
(52 reference statements)
4
65
0
Order By: Relevance
“…In our study, Caco-2 cells responded to quercetin by increasing the cytosolic GSH level, supporting the results of a previous study (44). In HT-29 cells, curcumin was found to significantly increase GSH content after no more than 3 h (45), and 2 studies indicated a raised GSH level after treatment with quercetin at a concentration of 10 µM (44,46). In contrast to curcumin and quercetin, EPA was found to cause a 20% reduction of GSH after 24 h of treatment (47).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, Caco-2 cells responded to quercetin by increasing the cytosolic GSH level, supporting the results of a previous study (44). In HT-29 cells, curcumin was found to significantly increase GSH content after no more than 3 h (45), and 2 studies indicated a raised GSH level after treatment with quercetin at a concentration of 10 µM (44,46). In contrast to curcumin and quercetin, EPA was found to cause a 20% reduction of GSH after 24 h of treatment (47).…”
Section: Discussionsupporting
confidence: 94%
“…This prooxidant activity could be due to an excessively high tested concentration as observed by uptake data, by prolonged incubation time in culture media (24 hours) used in the present study, in which H 2 O 2 production is probably induced. Hydrogen peroxide production was already demonstrated in previous studies in which other polyphenols have been used in different cell systems [61, 62, 81]. The H 2 O 2 production was assessed by Odiatou et al [81] on the two main olive polyphenols (hydroxytyrosol and oleuropein) incubated in the culture media and was observed as being dependent upon the presence of sodium bicarbonate in the medium.…”
Section: Discussionmentioning
confidence: 87%
“…Verbascoside stability was observed to be poor in the conditions tested (Figure 5). Oxidative degradation of phenolic compounds has been reported to proceed through auto-oxidative mechanism involving formation of H 2 O 2 [61, 62]. This increase in peroxides would explain the subsequent increase in CAT activity without an increase in SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ROS levels were measured using a cell-permeable fluorescent probe, 2,7-dichlorofluorescein diacetate (DCFH-DA) (Millipore, MA) as described previously with modifications (Bellion et al, 2009). Briefly, 100 ll of 5 Â 10 5 cell/ml HT-29 cells were seeded in a 96-well plate and cultured in DMEM complete media for 12 h. Then, cells were treated with 400 lg/ml dandelion leaf extract or 20 lg/ml chicoric acid in DMEM complete media for another 12 h. The cell monolayer was washed with PBS once and incubated with 100 ll of 10 lM fresh DCFH-DA in PBS for 30 min.…”
Section: Effects Of Extracts On Intracellular Reactive Oxygen Speciesmentioning
confidence: 99%